2023
DOI: 10.3390/microorganisms11040952
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infections in the Kingdom of Saudi Arabia, a Review

Abstract: Urinary tract infections (UTIs) are among the most common infections and are associated with an increased rate of antimicrobial resistance in Saudi Arabia. Better knowledge of the most common pathogens and their antimicrobial resistance patterns will be useful for creating new treatment guidelines. PubMed, Web of Science, Scopus, and Google Scholar were searched using suitable keywords to identify UTI publications until November 2022. Eligible studies were selected and analyzed. A total of 110 records were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The high resistance rate in ciprofloxacin in our study is in line with the findings in a study carried out in Kaiser Permanente WA, Seatle, USA, which stated that the ciprofloxacin-resistant UTI-causing strains of E. coli increased from 14.2% to 19.8% between 2015 and 2021 [ 16 ]. Comparable research conducted in Saudi Arabia revealed that bacteria were highly resistant to several routinely used antimicrobials, including ampicillin, ciprofloxacin, trimethoprim-sulfamethoxazole, and third-generation cephalosporins [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high resistance rate in ciprofloxacin in our study is in line with the findings in a study carried out in Kaiser Permanente WA, Seatle, USA, which stated that the ciprofloxacin-resistant UTI-causing strains of E. coli increased from 14.2% to 19.8% between 2015 and 2021 [ 16 ]. Comparable research conducted in Saudi Arabia revealed that bacteria were highly resistant to several routinely used antimicrobials, including ampicillin, ciprofloxacin, trimethoprim-sulfamethoxazole, and third-generation cephalosporins [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a greater prevalence of UTIs in pregnant women than in nonpregnant women. UTIs represent a major health problem in Saudi Arabia; they account for 10% of all infections in the country and are considered the second most common reason for emergency department admissions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) and local guidelines recommend the use of nitrofurantoin and cotrimoxazole as first-line therapies. As antimicrobial susceptibility patterns change rapidly, new resistant strains are emerging, and updates to these guidelines are needed periodically [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simple UTIs are more common and predictable, and the bacteria responsible for these infections are typically treatable. Escherichia coli is reported to account for approximately 80–90% of UTIs [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Kingdom of Saudi Arabia (KSA), UTIs significantly burden the healthcare system, constituting 10% of all infections and ranking as the second most common cause of emergency department admissions [ 1 , 2 , 3 , 8 , 9 ]. Women, in particular, are susceptible to UTIs, with approximately 60% estimated to experience at least one UTI in their lifetime, making them more prone to these infections compared to men [ 9 ].…”
Section: Introductionmentioning
confidence: 99%